Karyotype, chromosome structure, reproductive modalities of three Southern Eurasian populations of the common lacertid lizard, Zootoca vivipara (Jacquin, 1787) - Larissa Kupriyanova; Alex Kuksin; Gaetano Odierna (Acta Herpetologica, 2008)
According to a hypothesis of the evolution of viviparity the lacertid lizard Zootoca vivipara, rare relict oviparous populations of the species might occur in southern-eastern part of its distribution area. Such a hypothesis has been verified by comparing the karyotype, chromosome structure, and reproductive modality of three populations of south-eastern part of Russia, including Altai and neighbouring regions, where small territories remained isolated during the Pleistocene cooling and where Pleistocenic fossils of Z. vivipara have been found. The chromosomal study was carried out by conventional staining method and banding methods, namely C-banding and sequential staining of C-banding+ fluorochromes, CMA3 and DAPI. All studied females displayed viviparous reproductive modality and showed a karyotype of 2N = 35 acrocentric chromosomes, with a Z1Z2W sex chromosome system. Chromosome W was subtelocentric. No inter-population variability on karyotype and heterochromatin distribution and composition was observed. From the obtained data the three studied south-eastern Russian viviparous populations belong to the Russian viviparous form of Z. v. vivipara.